On the applicable law to detrimental acts, third party payments and “assignment” of claims in cross border insolvency proceedings: comments on CJEU Judgement C-73/20 frerichs “nemo datur quod non habet” - Ruiz Martín, Anna María (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
In this preliminary ruling (C-73/20), the Court of Justice of the European Union (CJEU) faces again (as did in former case law), the issue of what law is applicable to detrimental acts within the course of a cross border insolvency proceeding. On this occasion, the CJEU analyses how and when, –according to the EU Private International Law (EU PIL) at hand for those proceedings, i.e.: the lex spe-cialis (articles 4 and 13 Insolvency Regulation) and the lex generalis (article 12 para 1 lit a Rome I Re-gulation)–, which one is of application to determine the law applicable to acts which can be considered as “detrimental” to all the creditors. With other words, whether it would be applicable to the detrimental act, the lex concursus which governs the insolvency proceedings as a whole or the lex contractus which governs the law to the contract which led in these detrimental acts. However, the particularity of this case which is highly significant is grounded in the different relationships of the parties as a consequence of an “alleged” assignment between the insolvent company, the original debtor and an outsider creditor to this cross-border insolvency proceeding. Something that the CJEU did not pore it over as expected.